Spiritual Pedagogy in the Digital Age: A Framing Analysis of Religious Education on the Instagram Account @hijaberscommunityofficial - Fika Amelia Azzahro (Zamzami Scholar Publishing, 2026)
This study examines the transformation of religious education in the digital age through a public pedagogy study of the Instagram account @hijaberscommunityofficial. This platform has evolved into a spiritual learning ecosystem that facilitates the construction of religious identity, the transition of educational authority, and the formation of interactive learning communities. By integrating Robert Entman’s framing analysis and the Community of Inquiry (CoI) framework, this study dissects visual instructional design and the dynamics of modern Muslim women’s literacy interactions. The research findings confirm the account manager’s success in executing Teaching Presence through framing cultural vulnerability issues and offering a spiritual recovery curriculum grounded in Islamic teachings. This pedagogical strategy measurably triggers the emergence of Social Presence in the form of communal affective support, as well as Cognitive Presence in the form of the internalization of rational religious understanding. This ecosystem consistently stimulates the realization of digital moral discipline and solidarity among Muslim women. This research confirms the crucial role of social media as an arena for inclusive religious pedagogy, while enriching academic discourse at the intersection of digital literacy, cyber instructional design, and gender character education.